«FATIGUE UKRAINE». GORDIAN EUROPEAN SECURITY KNOT - Victor I. Mironenko (Научно-аналитический вестник Института Европы РАН, 2022)
The article prepared in the Center of Ukrainian Studies of the Institute of Europe of the Russian Academy of Sciences is devoted to the most acute and dangerous international crisis in Europe – the Ukrainian. By the time it was written, it was getting used to, a little tired of it, but he recalled himself again with predictions and the expectation of a great war in Eastern Europe. In the article some of the insufficiently visible features, conditions and means of resolving it has been highlighted. It concludes that its causes and significance go far beyond Ukrainian post-Soviet transit and Ukrainian-Russian inter-State relations. The depth and duration of it, the unsuccessful attempts to resolve it, have once again attested to the dangerous distance between political thinking and the changes that have taken place in Europe and the world. That the old security system and the mechanisms for dealing with such crises are obsolete. The Ukrainian crisis will either completely destroy it, setting international relations back to the state they were in before Helsinki, or it will become a point from which not only a new security system must and can be constructed, but also a new, more just and sustainable world order.